Acidic pH and capsaicin activate mechanosensitive group IV muscle receptors in the rat - Hoheisel, Ulrich; Reinöhl, Jochen; Unger, Thomas; Mense, Siegfried (Pain, 2004)
Strenuous exercise of muscle as well as inflammation and ischaemia are associated with tissue acidosis. However, so far, nothing is known about the sensitivity to hydrogen ions of slowly conducting muscle afferent units. The study investigated if acid-sensing ion channels, e.g. the polymodal acid/capsaicin-sensitive vanilloid receptors, were present on unmyelinated (group IV) muscle afferent units of the gastrocnemius-soleus muscle of the rat. Intramuscular injections of acidic phosphate buffer pH 6 excited 56.0% of the group IV units. A similar proportion (54.29%) was activated by capsaicin (655 μM). Tests of the same unit with both adenosine triphosphate at neutral pH (ATP, 7.6 mM; pH 7.4) and acidic phosphate demonstrated that most acid-sensitive units were also excited by ATP at neutral pH. The data show that (1) a high proportion of group IV muscle receptors are responsive to an increased extracellular hydrogen ion concentration, and (2) a subpopulation of these units are sensitive to both acidic pH and ATP.
Gesehen am 08.09.2017